Inhibitors in Patients with Congenital Bleeding Disorders Other Than Hemophilia - Franchini, Massimo; Marano, Giuseppe; Mengoli, Carlo; Piccinini, Vanessa; Pupella, Simonetta; Vaglio, Stefania; Liumbruno, Giancarlo Maria (Seminars in Thrombosis and Hemostasis, 2018)
The most worrying complication of replacement therapy for severe hemophilia A and B is currently the occurrence of inhibitory alloantibodies against infused factor VIII and factor IX, respectively. Inhibitors compromise the management of hemorrhage in affected patients, with a considerable increase in complications, disability, and costs. While these alloantibodies have been extensively studied in the past years in hemophilia A and B, those occurring in patients with other inherited bleeding disorders are less well characterized and still poorly understood, mostly due to the rarity of these hemorrhagic conditions. This narrative review will deal with inhibitors arising in patients with inherited bleeding disorders other than “classical” hemophilia, focusing in particular on those developing in patients with congenital deficiency of coagulation factor V, factor VII, factor XI, and factor XIII.
Keywords: inherited bleeding disorders; alloantibodies; congenital; inhibitors